Unblocked Electron Channels Enable Efficient Contact Prelithiation for Lithium‐Ion Batteries - Yue, Xin‐Yang; Yao, Yu‐Xing; Zhang, Jing; Yang, Si‐Yu; Li, Zeheng; Yan, Chong; Zhang, Qiang (Advanced materials (Weinheim), 2022)
Contact prelithiation is strongly considered for compensating the initial capacity loss of lithium‐ion batteries, exhibiting great potential for ultralong cycle life of working batteries and the application of large‐scale energy‐storage systems. However, the utilization of the sacrificial Li source for contact prelithiation is low (<65%). Herein the fundamental mechanism of contact prelithiation is described from the perspective of the Li source/anode interfaces by regulating the initial contact state, and a clear illustration of the pathogeny for capacity attenuation is successfully delivered. Specifically, creating plentiful electron channels is an access to making contact prelithiation with a higher Li utilization, as the mitigated local current density that reduces the etching of Li dissolution and SEI extension on electron channels. A vacuum thermal evaporation for depositing the Li film enables the contact interface to possess an adequate electron channel construction, rendering a Li utilization of 91.0%, and the dead Li yield is significantly reduced in a working battery. The isolation of electron channels leads to a low Li source utilization for contact prelithiation, and the resultant “dead Li” greatly degrades battery performance. Creating more electron channels at the Li source/anode interface not only dissipates the local current density to stabilize the electron channels, but also promotes the reaction kinetics, thus supporting an improved Li utilization for contact prelithiation.